2021
DOI: 10.2147/idr.s323490
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Clinical Outcomes of Osteoarticular Infections Among Pediatrics Admitted to Jimma University Medical Center, Ethiopia: A Prospective Observational Study

Abstract: Background: Despite the high burden of osteoarticular infections in sub-Saharan Africa, there is a paucity of data regarding the osteoarticular infections management approach and clinical outcomes in the region. Hence, this study aimed to evaluate a management protocol, clinical outcomes, and its determinants among pediatric patients with osteoarticular infections. Methods: A pediatric patient admitted to Jimma University Medical Center (JUMC), Ethiopia, with a diagnosis of osteoarticular infections was enroll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“… 10 – 12 COM is also a problem and a challenge to the orthopedic surgeons and the health facilities, as it is never truly cured. 13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 – 12 COM is also a problem and a challenge to the orthopedic surgeons and the health facilities, as it is never truly cured. 13 …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] COM is also a problem and a challenge to the orthopedic surgeons and the health facilities, as it is never truly cured. 13 In Ethiopia, COM accounted for 30% of admissions to Tikur Anbessa Specialized Hospital (TASH), Addis Ababa, Ethiopia. 9 Despite the significant burden imposed by COM, little research has been conducted in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In sub-Saharan Africa, a study by Mamo et al in Ethiopia found that poor outcomes were associated with the presence of a comorbidity and the use of combination antibiotics (ceftriaxone and metronidazole). 8 Mue et al in Nigeria suggested that complications in their cohort of patients may be due to a long duration of symptoms and delay in treatment, underlying systemic and immunosuppressive illnesses, joint site (especially hip and shoulder), and the virulence of the organisms (e.g., Staphylococcus aureus and Gram-negative bacilli). 9 Unfortunately, no univariate analyses were performed on these proposed associations.…”
Section: Introductionmentioning
confidence: 99%